The Moduli Space of 3|2-Dimensional Complex Associative Algebras - Penkava, Michael; Wagner, Jory; Payne, Carolyn; Gonzales, Tyler (My University, 2018)
A complex associative algebra is a vector space over the complex numbers equipped with a multiplication operation. The purpose of this study was to investigate the 3|2 dimensional complex associative algebras, constructing the moduli space of isomorphism classes of such algebras using the notion of extensions of algebras of lower dimension.
Color poster with text and models.
Keywords: Posters; Mathematics; Algebra; Complex associative algebra